Ang hudhud ni Rio Alma - Baquiran, Romulo P., Jr.; Baquiran, Romulo P., Jr. (Manila : National Commission for Culture and the Arts, 2009)
A collection of poems by National Artist for Literature, Virgilio S. Almario and criticisms by five known Filipino writers.
In Tagalog.